Anthropometric Measurement of Mastoid Process Using Multidetector Computed Tomography - Basnet, Prabhat; Upadhyay, Hari Prasad; Chaulagain, Rajib (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Mastoid process is one of the most important landmark of the skull. It is a part of temporal bone and contains air filled space which is called mastoid air cells. It is also an attachment of different neck muscles. Normal measurement of the mastoid process is very important for surgeons' point of view. This study was aimed to assess the normal dimension of mastoid process. Methods The study was a descriptive cross-sectional study conducted on 104 patients, at Department of Radiology and Imaging, College of medical sciences, Bharatpur, Nepal. All CT examinations were performed using Toshiba 160 slice CT scanner. The data was analyzed using Statistical Package for the Social Sciences (SPSS) version 16 (SPSS, Inc., an IBM Company, Chicago, IL). Descriptive statistics was used to analyze the data. Results Among the 104 patients who participated in the study, 38 (36.5%) were male and 66 (63.5%) were female. All the measurements of mastoid process taken in males were higher than in females except the anterior inclination angle which was more in female on both right and left side. The volume of mastoid process in males was 14.16±5.3 and 14.69±6.6 on right and left side respectively while in female it was less. Conclusions The present study estimated the normal dimension of mastoid process. The normal dimension of mastoid process in male is larger than in females.